2022
DOI: 10.1186/s42836-021-00104-5
|View full text |Cite
|
Sign up to set email alerts
|

The direct anterior approach to the hip: a useful tool in experienced hands or just another approach?

Abstract: The direct anterior approach (DAA) to the hip was initially described in the nineteenth century and has been used sporadically for total hip arthroplasty (THA). However, recent increased interest in tissue-sparing and small incision arthroplasty has given rise to a sharp increase in the utilization of the DAA. Although some previous studies claimed that this approach results in less muscle damage and pain as well as rapid recovery, a paucity in the literature exists to conclusively support these claims. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Furthermore, this approach effectively circumvents injury to the external rotator muscles inherent in the PA, thereby safeguarding therapeutic efficacy and enhancing operative safety. [11][12][13][14] In clinical practices, the daily life and movement of patients who need hip replacement are greatly restricted, and their self-care ability is relatively poor. Hip replacement can effectively improve the patients' hip joint limitation, enhance their self-care ability, and help the patients to establish the confidence in treatment, as well as to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this approach effectively circumvents injury to the external rotator muscles inherent in the PA, thereby safeguarding therapeutic efficacy and enhancing operative safety. [11][12][13][14] In clinical practices, the daily life and movement of patients who need hip replacement are greatly restricted, and their self-care ability is relatively poor. Hip replacement can effectively improve the patients' hip joint limitation, enhance their self-care ability, and help the patients to establish the confidence in treatment, as well as to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this approach effectively circumvents injury to the external rotator muscles inherent in the PA, thereby safeguarding therapeutic efficacy and enhancing operative safety. [11–14]…”
Section: Discussionmentioning
confidence: 99%
“…The commonly reported surgical technique of the DAA has been applied [ 18 , 19 ]. In detail, patients were placed in supine position and surgery was performed on a standard operation table.…”
Section: Methodsmentioning
confidence: 99%
“…Realyvasquez et al evaluated direct anterior approach by reviewing the literature and concluded that the published literature remains inconclusive about the superiority of these approach. Besides the complications associated with the approach and mentioned above, there is contraindication in using it for the patients with higher body mass index 22 . Hardinge approach has no contraindication regarding the obese patients due to versatility and extensibility and we didn't recorded risk of complications (longer operative time, increased operative bleeding, intraoperative fracture or nerve injury) related to the surgery time for these patients.…”
Section: Discusionmentioning
confidence: 99%